2019
DOI: 10.1002/aenm.201900162
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antireflective Coating CYTOP, Immersion Oil, and Sensitizer Selection in Fabricating a 2.3 V, 10% Power Conversion Efficiency SSM‐DSC Device

Abstract: for maximizing power output from an illuminated area is through the use of multijunction solar cell constructs. [3] Recently, we put forward the first sequential series multijunction dye-sensitized solar cell (SSM-DSC), which could power solarto-fuel conversion directly from a single illuminated area. [4] This construct showed solar-to-fuel conversion efficiencies of up to 3% for CO 2 to CO and H 2 O to H 2 and O 2 reactions in the seminal report of a purely DSC-based technology powering these processes from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The transmittances of the CYTOP films at 2000, 3000, and 4000 rpm were 89.7%, 91.2%, and 91.3% at 550 nm, respectively. Interestingly, the transmittance of the bare quartz substrate (88.9%) was slightly lower than that CYTOP coated quartz, in agreement with a previous study . Additionally, we observed no absorbance peaks of core@shell QDs film in the green line spectrum of inset in Figure f, compared to the blue line spectrum (CYTOP/QD film).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The transmittances of the CYTOP films at 2000, 3000, and 4000 rpm were 89.7%, 91.2%, and 91.3% at 550 nm, respectively. Interestingly, the transmittance of the bare quartz substrate (88.9%) was slightly lower than that CYTOP coated quartz, in agreement with a previous study . Additionally, we observed no absorbance peaks of core@shell QDs film in the green line spectrum of inset in Figure f, compared to the blue line spectrum (CYTOP/QD film).…”
supporting
confidence: 92%
“…Interestingly, the transmittance of the bare quartz substrate (88.9%) was slightly lower than that CYTOP coated quartz, in agreement with a previous study. [38] Additionally, we observed no absorbance peaks of core@shell QDs film in the green line spectrum of inset in Figure 2f, compared to the blue line spectrum (CYTOP/QD film). QDs film uncoated with CYTOP on the Corning glass was exposed to air for the tranmittance measurement, and we found that absorbance peaks of QDs film without CYTOP were disappeared, indicating unstability of InP@ZnSeS QDs in air.…”
mentioning
confidence: 77%
“…D35, B11, and Black Dye DSCs were prepared as reported in the literature. 38,56,57 For MK2 (second subcell), B11 (bottom subcell), and AP25 + D35 (bottom subcell) devices, the electrodes were prepared as recently reported. 33,36 Counter Electrode Preparation and Device Assembly.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The use of insulating metal oxides such as MgO and Al 2 O 3 between the dye and semiconductor to reduce recombination rates has been an active area of research within the DSC field. ,,, , More recently, fluorinated molecules with silyl anchors have been employed as fluorinated self-assembled monolayers (F-SAMs) that coadsorb to the semiconductor in the presence of dyes to reduce recombination sites and lower surface tension (i.e., give a reduction in noncovalent bonding or electrolyte adhesion to the TiO 2 surface). , This study seeks to compare these two approaches using a transition metal-based RS ([Co­(bpy) 3 ] 3+/2+ ) used widely in high performing devices and a ruthenium sensitizer ( B11 ) that is one of the highest PCE ruthenium dyes known using I 3 – / I – (Figure ). Notably, with the MgO insulating approach, significant effects on the rates of the injection, BET reaction, and recombination reactions are expected because each of these electron transfers crosses the insulating barrier.…”
Section: Introductionmentioning
confidence: 99%